Characterization of an Immunoglobulin Binding Protein (IbpM) From Mycoplasma pneumoniae - Blötz, Cedric; Singh, Neil; Dumke, Roger; Stülke, Jörg (Frontiers in Microbiology, 2020)
Bacteria evolved many ways to invade, colonize and survive in the host tissue. Such complex infection strategies of other bacteria are not present in the cell-wall less Mycoplasmas. Due to their strongly reduced genomes, these bacteria have only a minimal metabolism. Mycoplasma pneumoniae is a pathogenic bacterium using its virulence repertoire very efficiently, infecting the human lung. M. pneumoniae can cause a variety of conditions including fever, inflammation, atypical pneumoniae and even death. Due to its strongly reduced metabolism, M. pneumoniae is dependent on nutrients from the host and aims to persist as long as possible, resulting in chronic diseases. Mycoplasmas evolved strategies to subvert the host immune system which involve proteins fending off immunoglobulins (Igs). In this study, we investigated the role of MPN400 as the putative factor responsible for Ig-binding and host immune evasion. MPN400 is a cell-surface localized protein which binds strongly to human IgG, IgA and IgM. We therefore named the protein MPN400 immunoglobulin binding protein of Mycoplasma (IbpM). A strain devoid of IbpM is slightly compromised in cytotoxicity. Taken together, our study indicates that M. pneumoniae uses a refined mechanism for immune evasion.